PENGARUH FAMILY STRUCTURE (INTACT FAMILY DAN DISRUPTED FAMILY) TERHADAP PERILAKU COMPULSIVE BUYING PADA MAHASISWA DI UNIVERSITAS RIAU DENGAN FAMILY STRESSORS SEBAGAI VARIABEL MEDIASI - Siti Kariyah; Gatot Wijayanto; Marhadi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted at the University of Riau in order to determine the effect of family structure (intact family and disrupted family) toward compulsive buying in students at University of Riau with family stressors as a mediate variable. The populations in this research were 140 students at the University of Riau which consisted of 82 students from intact families (intact family) and 58 students from families who experience problems (disrupted family). To perform the analysis used different test, there are; One Way ANOVA, Path Analysis (Path analysis) and linear regression. From the analysis, we can concludes that students at University of Riau from families with impaired (disrupted family) tend to be compulsive buying behavior than students of University of Riau who come from intact families (intact family). In the University of Riau, female students has a greater tendency to be a compulsive buyer than the male students. There are no difference compulsive buying Riau University students who come from families who experience problems (disrupted family) such as divorce, death and separation. Family stressors mediate the effect of family structure toward compulsive buying on students of University of Riau. Family stressors affect compulsive buying behavior of students at the University of Riau.Keywords : Family Structure, Family Stressors, Compulsive Buying